Pengaruh Lingkungan terhadap Kinerja Keuangan Industri Kecil Perkayuan di Kaltim - Irwansyah - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aims to analyses direct and indirect the influence of general environment, toward the financial performance of small scale timbering industrial at East Kalimantan through Internal Environment and Business Strategic. This research is conducted by survey method toward the owner of small scale timbering industrial at Eastern Kalimantan Province. The data were collected by interviewing method, which was giving questionnaire about 115 industrial small scale timbering industrial’s owners. The research data analyzed by using Structural Equation Model (SEM). This observational result points out that the performance of small scale timbering industrial influenced by general environment after empowering by internal environment, and business strategic. Return on assets as dominant indicator in small scale timbering industrial’s financial performance, advance of technology as dominant indicator in general environment, labor as dominant indicator internal environment, and differentiation as dominant indicator in business strategic.Keywords: Environment, Business Strategic, and The Financial Performance of Small Scale Timbering Industrial.